2021
DOI: 10.1002/mp.14637
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo modeling of the influence of strong magnetic fields on the stem‐effect in plastic scintillation detectors used in radiotherapy dosimetry

Abstract: Purpose To investigate the impact of strong magnetic fields on the stem‐effect in plastic scintillation detectors (PSDs) using Monte Carlo methods. Methods Prior to building the light guide model, the properties of the Čerenkov process in GEANT4 were investigated by simulating depth‐dose and depth‐Čerenkov emission profiles in water as functions of Čerenkov process input parameters. In addition, profile simulations were performed for magnetic field strengths ranging from 0 T to 1.5 T. A PMMA light guide was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition, Simiele et al. studied the characterization of the intensity and spectral response changes in a plastic scintillation detector (PSD) as a function of magnetic field strength 19,20 and its impact on the stem‐effect in plastic scintillation detectors 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Simiele et al. studied the characterization of the intensity and spectral response changes in a plastic scintillation detector (PSD) as a function of magnetic field strength 19,20 and its impact on the stem‐effect in plastic scintillation detectors 21 …”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, Simiele et al studied the characterization of the intensity and spectral response changes in a plastic scintillation detector (PSD) as a function of magnetic field strength 19,20 and its impact on the stem-effect in plastic scintillation detectors. 21 An ideal detector should have good reproducibility, repeatability, linearity, high sensitivity and detection efficiency with no angular dependence. In addition, it should be easy to position with a stable signal over time with no dependency on radiation energy for small size fields.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the chromatic removal method is a sufficient stem removal technique even in a dynamic setting with an MR field included. Previous studies have found that the Cerenkov component of the stem effect changes with an added magnetic field, but that the spectral distribution stays the same (Maraghechi et al, 2020;Simiele et al, 2020Simiele et al, , 2021. Other studies have successfully corrected for the stem effect in static setups (Therriault--Proulx et al, 2018;Stefanowicz et al, 2013), while this study is the first, to our knowledge, that shows the removal of the stem effect for a dynamic setup in an MR-Linac where the amount of stem (in beam fiber) changes during the scan.…”
Section: Suitability Of the Detector Systemmentioning
confidence: 66%